Laser velocimetry and particle sizing - Thompson, H. Doyle; Stevenson, Warren H.; United States. Air Force. Office of Scientific Research; International Workshop on Laser Velocimetry (3rd : 1978 : Purdue University) (New York : Hemisphere, 1979)
05